IBD 2 A comparison of the effectiveness of a generic oral nutritional supplement with a specialised formula in the treatment of active paediatric crohn's disease. (12th September 2022) - Wands, David; Dawson, Robin; Logan, Michael; Meredith, Joseph; Efklides, Sarah; Benn, Laura; Henderson, Paul; Bremner, Gillian; Grant, Heather; Armstrong, Kat; Gerasimidis, Kostas; Wilson, David; et al.
Abstract : Background and Aims: Exclusive enteral nutrition (EEN) is the recommended induction treatment of mild to moderate active paediatric Crohn's Disease (CD). This study compared outcomes of two proprietary polymeric formulas. Treatment effectiveness was examined along with practical aspects of formula delivery and differences in estimated treatment costs. Methods: Data were retrospectively collected from CD patients who received a generic oral nutritional supplement (Fortisip) across two centres (RCH, Melbourne and RHSC, Edinburgh). This was compared to a prospective cohort (RHC, Glasgow) who used a specialised formula (Modulen IBD). The data collected included patient demographics, remission rates, biochemical markers, administration method and anthropometrics. The estimated treatment cost was performed by comparing price per kcal between each formula. Results: 171 patients were included (106 Fortisip, 65 Modulen IBD, 70/171 female; median age 13.3 yrs.). No difference was demonstrated in remission rate (Fortisip n=67/106 [63%] vs Modulen IBD n=41/64 [64%], p=0.89), non-adherence rate (Fortisip n=7/106 [7%] vs Modulen IBD 3/64 [5%], p=0.57) or method of administration (NGT Fortisip use n=16/106 [12%] vs Modulen IBD 14/65 [22%], p=0.31). There was no difference in reduction of biochemical disease markers between the groups (CRP p=0.13, ESR p=0.49, FC p=0.94). However, there was a cost-saving of around £500/patient/course if the generic oral nutritional supplement was used. Conclusions: The generic oral nutritional supplement and specialised formulas both had similar clinical effectiveness in induction of remission in paediatric CD. However, there is considerable cost saving when using a generic oral nutritional supplement.